OA01.16. Effects of drakshavaleha on weight and crown-rump length in developing mice embryo - Kumar, Sunil (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Cyclophosphamide (CP) causes stunting in size and loss of body weight of the pups when injected intra-peritoneal (10 mg/kg) to pregnant mice on day 11 of gestation. Due to anti-anaemic properties and nutritional values, Drakshavaleha has been used as a Naimittika Rasayana (promoter of specific vitality in specific disease) by some of the Ayurvedic physicians in Rajasthan to a woman during her pregnancy expecting a good health of both mother and her offspring. The objective of the study was to investigate the protective effect of Drakshavaleha against CP induced growth retardation in mice pups in the terms of body weight and CR (crown-rump) length. METHOD: Group I (Control): Pregnant mice (n=10) received 0.2 ml of vehicle (distilled water) intra-peritoneal on day 11 of pregnancy. Group II (Drakshavaleha): Pregnant mice (n=10) received Drakshavaleha (16g/kg) orally from day ‘0’ to day ‘18’ of pregnancy. Group III (CP): Pregnant mice (n=10) received Cyclophosphamide (10mg/kg) intra-peritoneal on day 11 of pregnancy. Group IV (CP + Drakshavaleha): Pregnant mice (n=10) received CP (10mg/kg) intra-peritoneal on day 11 under cover of Drakshavaleha (16 g/kg) orally from day ‘0 to day 18’ of pregnancy. RESULT : Drakshavaleha (alone) increases the size and weight of the pups when given to mother mice during gestation period and the difference between the two groups (Group III and Group IV) is statistically significant (p<0.001). CONCLUSION: In the present context Drakshavaleha can be conceived to be a Naimittika Rasayana to a woman during her pregnancy to obtain a healthy progeny.